2021
DOI: 10.1002/hbm.25546
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic changes in a spaceflight analog are associated with brain functional reorganization

Abstract: Following long‐duration spaceflight, some astronauts exhibit ophthalmic structural changes referred to as Spaceflight Associated Neuro‐ocular Syndrome (SANS). Optic disc edema is a common sign of SANS. The origin and effects of SANS are not understood as signs of SANS have not manifested in previous spaceflight analog studies. In the current spaceflight analog study, 11 subjects underwent 30 days of strict head down‐tilt bed rest in elevated ambient carbon dioxide (HDBR+CO2). Using functional magnetic resonanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…At the same time, a decrease in connectivity at rest after SF in the right insula which is part of the vestibular cortex indicates changes in the integration of neurosensory information: vestibular, visual, and proprioceptive ( Demertzi et al, 2016 ). In a study by McGregor et al (2021a) during 30 days of HDBR + CO 2 , five out of 11 subjects showed a sign of spaceflight-associated neuro-ocular syndrome (SANS)—optic disc edema, that was accompanied by a slowdown in reaction and movement time after exposure when performing a visuomotor adaptation task using a joystick ( Banker et al, 2021 ) and greater visual contributions to balance ( Hupfeld et al, 2020 ). Interestingly, in six subjects without signs of SANS (NoSANS), there was a greater decoupling between the insula and the other regions within the network during the baseline phase, as well as a decrease in connectivity between the right posterior parietal cortex and clusters in bilateral insular cortices during HDBR + CO 2 ( McGregor et al, 2021a ).…”
Section: Head-down Bed Restmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a decrease in connectivity at rest after SF in the right insula which is part of the vestibular cortex indicates changes in the integration of neurosensory information: vestibular, visual, and proprioceptive ( Demertzi et al, 2016 ). In a study by McGregor et al (2021a) during 30 days of HDBR + CO 2 , five out of 11 subjects showed a sign of spaceflight-associated neuro-ocular syndrome (SANS)—optic disc edema, that was accompanied by a slowdown in reaction and movement time after exposure when performing a visuomotor adaptation task using a joystick ( Banker et al, 2021 ) and greater visual contributions to balance ( Hupfeld et al, 2020 ). Interestingly, in six subjects without signs of SANS (NoSANS), there was a greater decoupling between the insula and the other regions within the network during the baseline phase, as well as a decrease in connectivity between the right posterior parietal cortex and clusters in bilateral insular cortices during HDBR + CO 2 ( McGregor et al, 2021a ).…”
Section: Head-down Bed Restmentioning
confidence: 99%
“…In a study by McGregor et al (2021a) during 30 days of HDBR + CO 2 , five out of 11 subjects showed a sign of spaceflight-associated neuro-ocular syndrome (SANS)—optic disc edema, that was accompanied by a slowdown in reaction and movement time after exposure when performing a visuomotor adaptation task using a joystick ( Banker et al, 2021 ) and greater visual contributions to balance ( Hupfeld et al, 2020 ). Interestingly, in six subjects without signs of SANS (NoSANS), there was a greater decoupling between the insula and the other regions within the network during the baseline phase, as well as a decrease in connectivity between the right posterior parietal cortex and clusters in bilateral insular cortices during HDBR + CO 2 ( McGregor et al, 2021a ). These observations are consistent with the results of Pechenkova et al (2019) , namely, indicating that such a decrease in connectivity may be associated with the theory of central adaptation, which downregulates vestibular input during space flight lessening sensory dissonance.…”
Section: Head-down Bed Restmentioning
confidence: 99%
“…Headward fluid shift, which is induced by HDT, is assumed to be one of the key factors of SANS (Gibson et al, 2012). In a spaceflight analog study, HDT posture and elevated ambient carbon dioxide induced optic disc edema in 5 of 11 subjects (McGregor et al, 2021). Although carbon dioxide was not elevated in our study, −30° HDT resulted in several symptoms, including piercing pain, blur acid, strain, eye burning, and dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that microgravity mediated cephalad fluid shift is the primary causative factor leading to increased intracranial pressure, however its exact pathophysiology remains unclear 29 30. The effect of spaceflight on brain structure is being investigated, but a connection between SANS and brain structure or function (cognition) is yet to be definitively established 28 31…”
Section: Effects Of Spaceflight On Select Physiological Systems and H...mentioning
confidence: 99%
“…SANS is currently the focus of intensive study; it remains unclear whether it could pose a serious risk to participants in future spaceflights of long duration exploration class missions or whether any pre-existing morphological, genetic or physiological factors might alter or help predict and mitigate this risk. The high-priority placed by space agencies in developing countermeasures and diagnosing SANS may lead to many terrestrial benefits including novel non-invasive methods of measuring intracranial pressure thereby allowing us to better diagnose and manage pathologies such as hydrocephalus and idiopathic intracranial hypertension 28 30–34…”
Section: Effects Of Spaceflight On Select Physiological Systems and H...mentioning
confidence: 99%